Composite film paper material and preparation method thereof
By using the combination and crosslinking technology of polylactic acid, polybutylene terephthalate, esterified hydrophobic vapor phase silica, polyether polyol and quinoline in composite film paper materials, the problems of insufficient barrier properties and unsatisfactory material degradation properties of existing composite film paper materials are solved, and the combination of high barrier properties and good mechanical properties is achieved, and the material is easy to recover.
Patent Information
- Application Number
- CN202510050230.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-13
AI Technical Summary
While improving barrier properties, the existing composite film paper materials are difficult to meet the high barrier effect without relying on the aluminum film layer, and the degradation performance of the material is not ideal.
The composite film layer is composed of materials such as polylactic acid, polybutylene adipate terephthalate, esterified hydrophobic vapor-phase silica, polyether polyol and quinoline. The crosslinking of the esterified hydrophobic vapor-phase silica with other materials is formed to form a tight structure to improve barrier properties.
It significantly improves the barrier properties of composite film paper materials, while maintaining good mechanical properties, and the material is easy to recycle and meets environmental protection requirements.
Smart Images

Figure BDA0005239756850000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging materials, and specifically relates to a composite film paper material and a preparation method thereof. Background Art
[0002] Composite film and paper materials are packaging materials made of two or more materials of different properties through a specific process. They have excellent physical properties, chemical properties and barrier properties and are widely used in the field of packaging material technology in industries such as food, medicine, and electronic products. At present, the disposable non-degradable plastic products commonly used in packaging materials include: non-biodegradable polymer materials such as polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), ethylene-vinyl acetate copolymer (EVA), and polyethylene terephthalate (PET). Therefore, the use of degradable plastics to prepare composite film and paper is the current development prospect.
[0003] CN108819411A discloses a packaging material with barrier function, including a barrier layer, a reinforcement layer, a protective layer and a printing layer, wherein the layers are hot-pressed and laminated by adhesives, wherein the barrier layer is a kraft paper aluminum-coated film, and the printing layer material is a biaxially oriented polyethylene film; the technical solution has a simple structure, reasonable design, low cost, excellent barrier properties, high mechanical strength, and good pressure resistance; however, the material used for the printing layer is a biaxially oriented polyethylene film, and although it has good properties, its degradation performance is not ideal, which is contrary to the challenges faced by the current society in plastic recycling and treatment. CN112937045A discloses a biodegradable high-barrier composite film material structure and its packaging bag. The composite film material includes a cellulose layer, a pure aluminum layer, and a PBAT layer from top to bottom, and the layers are combined together by adhesive composite film-forming technology. The performance of each film layer in this technical solution is complementary, and a composite film material with good surface wetting tension, heat resistance and heat sealability, and adapting to low-temperature freezing, high-barrier conditions and other performance requirements can be made. The degradable part has a degradation rate of more than 90%, which is energy-saving and environmentally friendly. Although this technical solution uses degradable materials, aluminum film is still used to compound with other film layers to improve the barrier properties of the composite film. The main means to improve the barrier properties of the composite film in the above two patents are to compound aluminum foil or pure aluminum with other film layers to enhance the barrier capacity of the composite film. However, the barrier properties of the composite film cannot meet the application of the composite film in the field of packaging material technology when PBAT, polyethylene and other materials are used alone in combination with other film layers.
[0004] Therefore, there is an urgent need to develop a new type of high barrier composite film that can achieve a high barrier effect without relying on the composite with an aluminum product film layer. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, one of the purposes of the present invention is to provide a composite film paper material, wherein the composite film layer has good compatibility and is easy to recycle; and the composite film paper has excellent barrier properties.
[0006] One of the purposes of the present invention is achieved by the following technical solution:
[0007] A composite film paper material comprises a composite film layer and a paper layer; the composite film layer comprises the following raw materials in parts by weight: 60 to 70 parts of polylactic acid, 20 to 30 parts of polybutylene terephthalate adipate, 5 to 8 parts of polyether polyol, 5 to 8 parts of esterified hydrophobic fumed silica, and 3 to 5 parts of quinoline; the esterified hydrophobic fumed silica is prepared by stirring fumed silica and acetyl chloride and then drying.
[0008] Furthermore, the usage ratio of the fumed silica and acetyl chloride is 1 g: 2-3 mL.
[0009] Furthermore, the stirring temperature is 10-20° C. and the stirring time is 2-3 h.
[0010] Furthermore, the drying temperature is 65-75° C. and the drying time is 2-3 hours.
[0011] Furthermore, the particle size of the fumed silica is 7 to 40 nm.
[0012] Furthermore, the polyether polyol is one of polytetramethylene glycol and polypropylene glycol.
[0013] Furthermore, the molecular weight of the polytetrahydrofuran diol is 250-3000, and the molecular weight of the polypropylene glycol is 1000.
[0014] Furthermore, the molecular weight of the polytetrahydrofuran diol is 1000.
[0015] Furthermore, the weight average molecular weight of the polylactic acid is 20,000 to 30,000, and the weight average molecular weight of the polybutylene terephthalate adipate is 60,000 to 80,000.
[0016] Furthermore, the thickness of the composite film layer is 48 μm.
[0017] A second object of the present invention is to provide a method for preparing a composite film paper material.
[0018] One of the purposes of the present invention is achieved by the following technical solution:
[0019] The preparation process of the composite film paper material comprises the following steps:
[0020] (1) mixing and stirring esterified hydrophobic fumed silica, polylactic acid, quinoline, and polyether polyol according to the weight ratio, and drying to obtain a mixture;
[0021] (2) adding polybutylene terephthalate adipate to the mixture of step (1), mixing evenly, and then melt-extruding through a twin-screw extruder, and plasticizing and granulating to obtain a composite film layer;
[0022] (3) Compounding the composite film layer and the paper layer in step (2) to obtain the composite film-paper material.
[0023] The esterified hydrophobic fumed silica, polylactic acid, quinoline and polyether polyol are stirred for a period of time to allow the components to be fully cross-linked under the action of quinoline, such as cross-linking of the esterified hydrophobic fumed silica with polylactic acid, cross-linking of polyether polyol with polylactic acid, cross-linking of the esterified hydrophobic fumed silica with polylactic acid and then with polyether polyol, and then melt-mixed with polybutylene terephthalate adipate for granulation.
[0024] Furthermore, in step (1), the stirring temperature is 60-65° C. and the time is 45-60 min; and the drying temperature is 65-75° C. and the time is 2-3 h.
[0025] Furthermore, the compounding process in step (3) includes hot pressing compounding and cold pressing flattening.
[0026] Furthermore, the temperature of the hot pressing is 138-142° C., and the pressure is 0.1-0.4 MPa; the temperature of the cold pressing is 20-25° C., and the pressure is 0.05-0.08 MPa.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention utilizes the active characteristics of the hydroxyl groups on the surface of fumed silica and successfully prepares esterified hydrophobic fumed silica by reacting it with acyl chloride. The present invention mixes esterified hydrophobic fumed silica, polylactic acid, quinoline and polyether polyols in a scientific proportion. The esterification of hydrophobic fumed silica can enhance its binding properties with PLA, PBAT and polyether polyols. Under the action of quinoline, the components can interact through ester exchange to form a tight structure. The hydrophobicity of esterified hydrophobic fumed silica and the tight structure formed between the components can significantly improve the barrier properties of the composite film paper material without affecting its mechanical properties. DETAILED DESCRIPTION
[0029] Below, in conjunction with specific embodiments, the present invention is further described. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0030] Example 1
[0031] A composite film-paper material comprises a composite film layer and a paper layer; the composite film layer comprises the following raw materials in parts by weight: 65 parts of polylactic acid (weight average molecular weight of 20,000-30,000), 25 parts of polybutylene terephthalate adipate (weight average molecular weight of 60,000-80,000), 7 parts of polytetramethylene glycol (molecular weight of 1,000), 7 parts of esterified hydrophobic fumed silica, and 4 parts of quinoline.
[0032] The preparation process of the esterified hydrophobic fumed silica comprises the following steps: adding fumed silica to acetyl chloride at a ratio of 1 g:2.5 mL of fumed silica (average particle size of 7 to 40 nm) and acetyl chloride, stirring at 15° C. for 2.5 h, and drying the mixed system at 70° C. for 2.5 h to obtain esterified hydrophobic fumed silica.
[0033] This embodiment also provides a method for preparing the composite film paper material, comprising the following steps:
[0034] (1) weighing esterified hydrophobic fumed silica and polytetrahydrofuran diol in a stirrer and stirring evenly, then successively adding polylactic acid and quinoline and stirring at 62° C. for 52 min, then drying at 70° C. for 2.5 h to obtain a mixture;
[0035] (2) weighing polybutylene terephthalate adipate and the mixture of step (1) and continuing to mix, and melt-extruded through a twin-screw extruder (30° C., 60° C., 120° C., 140° C., 150° C., 160° C. and 170° C.), and plasticizing and granulating the obtained material to obtain a composite film layer;
[0036] (3) The composite film layer and the paper layer in step (2) are first hot-pressed by a hot-pressing roller at 140° C. and 0.4 MPa for 3 seconds, and then flattened by a cold-pressing roller at 22° C. and 0.07 MPa to obtain a composite film-paper material. The thickness of the composite film layer is 48 μm.
[0037] Example 2
[0038] A composite film-paper material comprises a composite film layer and a paper layer; the composite film layer comprises 60 parts of polylactic acid (weight average molecular weight of 20,000-30,000), 20 parts of polybutylene terephthalate adipate (weight average molecular weight of 60,000-80,000), 5 parts of polypropylene glycol (molecular weight: 1,000), 5 parts of esterified hydrophobic fumed silica, and 3 parts of quinoline.
[0039] The preparation process of the esterified hydrophobic fumed silica comprises the following steps: adding the fumed silica to acetyl chloride at a ratio of 1 g:2 mL of fumed silica (particle size of 7 to 40 nm) and stirring at 10° C. for 3 h, and drying the mixed system at 65° C. for 2 h to obtain the esterified hydrophobic fumed silica.
[0040] This embodiment also provides a method for preparing the composite film paper material, comprising the following steps:
[0041] (1) Weighing esterified hydrophobic fumed silica and polypropylene glycol and stirring them in a stirrer, then sequentially adding polylactic acid and quinoline, stirring at 60° C. for 60 min, and then drying at 65° C. for 3 h to obtain a mixture;
[0042] (2) Weighing polybutylene terephthalate adipate and the mixture of step (1) and continuing to mix, melt-extrude through a twin-screw extruder (30° C., 60° C., 120° C., 140° C., 150° C., 160° C. and 170° C.), and plasticizing and granulating the obtained material to obtain a composite film layer;
[0043] (3) The composite film layer and the paper layer in step (2) are first hot-pressed by a hot-pressing roller at 138° C. and 0.1 MPa for 3 seconds, and then flattened by a cold-pressing roller at 20° C. and 0.05 MPa to obtain a composite film-paper material. The thickness of the composite film layer is 48 μm.
[0044] Example 3
[0045] A composite film-paper material comprises a composite film layer and a paper layer; the composite film layer comprises 70 parts of polylactic acid (weight average molecular weight of 20,000-30,000), 30 parts of polybutylene terephthalate adipate (weight average molecular weight of 60,000-80,000), 8 parts of polytetrahydrofuran diol (2 parts of polytetrahydrofuran diol with a molecular weight of 250, 6 parts of polytetrahydrofuran diol with a molecular weight of 3,000), 8 parts of esterified hydrophobic fumed silica, and 5 parts of quinoline.
[0046] The preparation process of the esterified hydrophobic fumed silica comprises the following steps: adding the fumed silica to acetyl chloride at a ratio of 1 g:3 mL of fumed silica (particle size of 7 to 40 nm) and stirring at 20° C. for 2 h, and drying the mixed system at 75° C. for 3 h to obtain the esterified hydrophobic fumed silica.
[0047] This embodiment also provides a method for preparing the composite film paper material, comprising the following steps:
[0048] (1) Weighing esterified hydrophobic fumed silica and polyether polyol and stirring them evenly in a stirrer, then sequentially adding polylactic acid and quinoline, stirring at 65° C. for 45 minutes, and then drying at 75° C. for 2 hours to obtain a mixture;
[0049] (2) weighing polybutylene terephthalate adipate and the mixture of step (1) and continuing to mix, and melt-extruded through a twin-screw extruder (30° C., 60° C., 120° C., 140° C., 150° C., 160° C. and 170° C.), and plasticizing and granulating the obtained material to obtain a composite film layer;
[0050] (3) The composite film layer and the paper layer in step (2) are first hot-pressed by a hot-pressing roller at 142° C. and 0.2 MPa for 3 seconds, and then flattened by a cold-pressing roller at 25° C. and 0.08 MPa to obtain a composite film-paper material. The thickness of the composite film layer is 48 μm.
[0051] Comparative Example 1
[0052] A composite membrane paper material, which differs from Example 1 in that the esterified hydrophobic fumed silica in step (1) is replaced by conventional hydrophobic fumed silica (model: HB-151).
[0053] Comparative Example 2
[0054] A composite membrane paper material, which differs from Example 1 in that quinoline in step (1) is omitted.
[0055] Test Example 1
[0056] The barrier properties and mechanical properties of the composite film and paper materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested; wherein, the water vapor permeability of each group of film and paper materials was measured according to GB / T1037-88 "Test method for water vapor permeability of plastic film and sheet - Cup method", and the test conditions were 38°C and 90% RH; the oxygen permeability of each group of film and paper materials was measured according to GB / T1038-2000 "Test method for gas permeability of plastic film and sheet - Pressure difference method", and the test conditions were 23°C and 0% RH; the tensile strength was tested according to GB / T1040.3-2006 standard, and the test rate was 250 mm / min, as shown in Table 1.
[0057] Table 1 Performance results of the membrane paper materials of Examples 1 to 3 and Comparative Examples 1 to 2
[0058]
[0059] It can be seen from Table 1 that the composite film paper materials prepared in Examples 1 to 3 of the present invention have excellent barrier effects, and their barrier effects on oxygen and water vapor are better than those in Comparative Examples 1 to 2, and they also have good tensile strength.
[0060] Comparative Example 1 uses conventional commercially available hydrophobic fumed silica, and the barrier effect of the material is slightly worse than that of Example 1. However, due to the poor bonding between the commercially available hydrophobic fumed silica and the matrix material, the mechanical properties of the material are lower than those of Example 1. In Comparative Example 2, no quinoline was added during the preparation of the composite film paper material, and the tensile strength of the material decreased.
[0061] Compared with Comparative Examples 1 to 2, Examples 1 to 3 of the present invention added the prepared esterified hydrophobic fumed silica and quinoline when preparing the composite film paper material. The esterification of the hydrophobic fumed silica can improve its binding properties with PLA, PBAT, and polyether polyols, and quinoline can make the components interact with each other to form a tight structure. The hydrophobicity of the esterified hydrophobic fumed silica and the tight structure formed between the components significantly improve the barrier properties of the material without affecting the mechanical properties.
[0062] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A composite film paper material, characterized in that: The invention comprises a composite film layer and a paper layer; the composite film layer comprises the following raw materials in parts by weight: 60 to 70 parts of polylactic acid, 20 to 30 parts of polybutylene terephthalate adipate, 5 to 8 parts of polyether polyol, 5 to 8 parts of esterified hydrophobic fumed silica, and 3 to 5 parts of quinoline; the esterified hydrophobic fumed silica is prepared by stirring fumed silica and acetyl chloride and then drying.
2. The composite film paper material according to claim 1, characterized in that: The usage ratio of the fumed silica and acetyl chloride is 1 g: (2-3) mL.
3. The composite film paper material according to claim 1, characterized in that: The stirring temperature is 10-20° C. and the stirring time is 2-3 h.
4. The composite film paper material according to claim 1, characterized in that: The drying temperature is 65-75° C. and the drying time is 2-3 hours.
5. The composite film paper material according to claim 1, characterized in that: The particle size of the fumed silica is 7 to 40 nm.
6. The composite film paper material according to claim 1, characterized in that: The polyether polyol is one of polytetrahydrofuran diol and polypropylene glycol.
7. The method for preparing a composite film paper material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing and stirring esterified hydrophobic fumed silica, polylactic acid, quinoline, and polyether polyol according to the weight ratio, and drying to obtain a mixture; (2) adding polybutylene terephthalate adipate to the mixture of step (1), mixing evenly, and then melt-extruding through a twin-screw extruder, and plasticizing and granulating to obtain a composite film layer; (3) Compounding the composite film layer with the paper layer to obtain the composite film-paper material.
8. The method for preparing the composite film paper material according to claim 7, characterized in that: In step (1), the stirring temperature is 60-65° C. and the time is 45-60 min; the drying temperature is 65-75° C. and the time is 2-3 h.
9. The method for preparing the composite film paper material according to claim 7, characterized in that: The compounding process in step (3) includes hot pressing compounding and cold pressing flattening.
10. The method for preparing the composite film paper material according to claim 7, characterized in that: The temperature of the hot pressing is 138-142° C., and the pressure is 0.1-0.4 MPa; the temperature of the cold pressing is 20-25° C., and the pressure is 0.05-0.08 MPa.
Citation Information
Patent Citations
Packaging material with barrier function
CN108819411A
Biodegradable high-barrier composite film material structure and packaging bag thereof
CN112937045A
Preparation method of immobilized alkaline ionic liquid catalyst
CN103406146A
High-barrier PLA / PBAT composite packaging film
CN112280260A
Composite modifier for improving barrier property of biodegradable film and preparation method thereof
CN115873383A
Cited By
Thermosetting phenolic resin for casting precoated sand and preparation method thereof
CN120399394A